2018
DOI: 10.3389/fpsyg.2018.00377
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairments in Fibromyalgia Syndrome: Associations With Positive and Negative Affect, Alexithymia, Pain Catastrophizing and Self-Esteem

Abstract: Fibromyalgia syndrome (FMS) is a chronic condition characterized by widespread pain accompanied by symptoms like depression, anxiety, sleep disturbance and fatigue. In addition, affected patients frequently report cognitive disruption such as forgetfulness, concentration difficulties or mental slowness. Though cognitive deficits in FMS have been confirmed in various studies, not much is known about the mechanisms involved in their origin. This study aimed to investigate the contribution of affect-related varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 90 publications
(136 reference statements)
14
92
3
7
Order By: Relevance
“…In this study, pain severity was positively associated with the number of PVT lapses. Our findings corroborated previous findings that patients with fibromyalgia who experience intense pain also have considerably poorer learning and memory performance (Wu et al., ), attention function and psychomotor processing speed (Galvez‐Sánchez, Reyes Del Paso, & Duschek, ; Park, Glass, Minear, & Crofford, ; Veldhuijzen et al., ) in cognitive domains compared with healthy individuals. However, we noted that pain severity was not associated with RT—a finding consistent with that of Coppieters et al.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, pain severity was positively associated with the number of PVT lapses. Our findings corroborated previous findings that patients with fibromyalgia who experience intense pain also have considerably poorer learning and memory performance (Wu et al., ), attention function and psychomotor processing speed (Galvez‐Sánchez, Reyes Del Paso, & Duschek, ; Park, Glass, Minear, & Crofford, ; Veldhuijzen et al., ) in cognitive domains compared with healthy individuals. However, we noted that pain severity was not associated with RT—a finding consistent with that of Coppieters et al.…”
Section: Discussionsupporting
confidence: 91%
“…Third, in relation to the cognitive–emotional behavior of fatigue, we found that difficulty thinking, difficulty concentrating, and negative emotions were the most referenced. According to previous research, many people dealing with fibromyalgia have problems maintaining their attention on the task at hand; therefore, they have problems memorizing as well as remembering [ 46 ]. Another reported problem is in relation to keeping track of a story’s plot while reading or watching television [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar maintenance effects have also been observed in other studies of mindfulness involving patients with FMS ( Grossman et al, 2007 ; Amutio et al, 2015a ; Cash et al, 2015 ; Van Gordon et al, 2017 ), as well as in studies following a similar approach to the model of mindfulness training adopted by the Meditación-Fluir intervention used in the present study ( Amutio et al, 2015a ; Franco et al, 2017 ). Some plausible explanations as to why the effects of mindfulness training programs are frequently maintained at follow-up assessments is that mindfulness is a technique that enhances positive affect and that it is relatively easy to integrate into daily life ( Davis and Zautra, 2013 ; Amutio et al, 2015b ; Galvez-Sánchez et al, 2018 ). This is an important consideration for patients with FMS that due to pain-related concentration deficits can experience difficulties in adapting to new psychological strategies ( Schmidt et al, 2011 ; Van Gordon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both poor quality sleep and pain can elicit catastrophizing thought and behavior patterns which in turn lead to the impairment of pain coping cognitive strategies ( Prados and Miró, 2012 ; Di Tella et al, 2018 ). Thus, sleep problems play an important role in the exacerbation of FMS symptoms and increase the likelihood of both depression and impaired physical and psychological functioning in this patient group ( Bigatti et al, 2008 ; González et al, 2010 ; Finan et al, 2013 ; Galvez-Sánchez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%